The Important Role of Strategic Management in Product Development - Shofie Afriati; Nur Fatwa; Rizqullah Rizqullah (International Journal Labs, 2026)
Product development in the digital and global era faces the dynamics of VUCA that demand organizations align long-term vision with innovation, resources, and governance decisions. Without a strategic framework, product development tends to be reactive, inconsistent, and vulnerable to market changes. Objective: This article describes the role of strategic management in product development as well as how management functions (POAC) and SWOT analysis can be used to strengthen competitiveness. The research uses a descriptive-analytical approach through literature studies and field research in the form of interviews, observations, and documentation on the Human Capital unit at a state-owned bank and supporting companies. The data are analyzed by reduction, presentation, and drawing conclusions. The findings confirm that integrated planning, organizing, actuating, and controlling guide product development decision-making, while SWOT helps map internal strengths and weaknesses and external opportunities and threats to formulate strategy priorities. From an Islamic perspective, the concept of al-governance emphasizes order, trust, and deliberation so that strategic practices have an ethical dimension that strengthens organizational discipline and accountability in decision-making. The VUCA framework clarifies the need for agility, scenario planning, data-driven decision-making, collaboration, and resilience for organizations to be able to adapt and innovate. Strategic management serves as a mechanism for aligning goals, strategies, and evaluations that improve organizational resilience and product development effectiveness in complex business environments.